Analisis Sistem Administrasi Pergudangan pada Facility, Workshop and Safety Development Department di PT United Tractors Tbk - Rosmaniar Rosmaniar; Henry Eryanto; Suherdi Suherdi (Asosiasi Peneliti Dan Pengajar Ilmu Sosial Indonesia, 2025)
The use of information technology is increasingly used by companies to manage the distribution of goods in a more effective and responsive way. This study aims to analyze the warehouse administration system at the Facility, Workshop and Safety Development Department at PT United Tractors Tbk. This study uses a qualitative method by collecting data through primary and secondary sources. Primary data sources are obtained through interviews, observations and documentation, while secondary data sources are obtained from journals, books or articles that discuss the warehouse administration system in a company. This study was analyzed using a descriptive method with data analysis techniques consisting of 4 (four) aspects starting from data collection, data reduction, data presentation to drawing conclusions. The results of the study indicate that by using Systems, Applications and Products in Data Processing (SAP) S / 4 HANA as a supporting facility from demand to distribution of goods and implementing the applicable System Operating Procedures (SOP) can increase the effectiveness of the department in meeting the needs that exist in the company's branches or sites so that the company's productivity is maintained. To overcome errors in the use of applications and human error in administration, this department needs to conduct training for employees to ensure that employees are able to use applications and implement System Operating Procedures (SOP) properly.